COLLABORATION AND PERFORMANCE IN FOREIGN MARKETS: THE CASE OF YOUNG HIGH-TECHNOLOGY MANUFACTURING FIRMS. - Shrader, R. C. (Academy of Management Journal, 2001)
This study employed transaction cost theory to explore factors moderating the relationship between collaboration and performance in foreign markets among a sample of international new ventures. Res...